PELAKSANAAN FUNGSI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) DALAM PENGELOLAAN JEMBATAN PENYEBERANGAN ORANG (JPO) DI KOTA PEKANBARU TAHUN 2018 - Putra, Andang Eka; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The presence of pedestrians at a certain level will result in sharp conflicts with the flow of vehicles which in turn results in traffic congestion and high levels of accidents, so that the provision of infrastructure and facilities for pedestrians who meet the requirements of security, comfort, safety and which can minimize conflicts between pedestrians and vehicles, minimizing traffic delays is needed. The crossing facility is an alternative in crossing problems used by pedestrians, one of which is the crossing bridge facility. Therefore, for the sake of pedestrian safety in Pekanbaru City, one of the efforts of the Pekanbaru City Government through the BPKAD of Pekanbaru City by managing the Crossing Bridge Person.This study aims to describe the implementation of the BPKAD function of Pekanbaru City in the management of People's Crossing Bridges, then also to find out the inhibiting factors for the non-optimal implementation of the Pekanbaru City BPKAD functions in the management of People's Crossing Bridges. The location of the study was conducted in Pekanbaru City, first at the BPKAD office in Pekanbaru City, Pekanbaru Transportation Agency. And 11 points of the Crossing Bridge location. Furthermore, data collection techniques were carried out with interviews and documentation.The results of this study are the implementation of the function of BPKAD Pekanbaru City in the management of People's Crossings as an effort to maintain JPO and pedestrian safety in Pekanbaru City has not been running optimally. This is caused by several factors such as the absence of a budget for JPO management, the private sector never submits JPO, and JPO ownership documents are incomplete. Keywords: managing pedestrian bridges, Pedestrian, function implementation, coordination